The relationship between currency and stock price between Malaysia and Thailand from year 2005 -2010 / Diawatul Adawiah Salbani - Salbani, Diawatul Adawiah (Faculty of Business and Management, 2011)
The study was conducted to find out the significant relationship between independent variables with dependent variable. The variables selected are currency (Malaysia and Thailand). The dependent variable is stock price (KLCI and AORD). The method used for this study is the regression analysis. The result then has been interpreted base on the correlation and coefficient correlation. The data used for the study are collected from the year 2005 to 2010. Base on the result, it was concluded that currency is significant to the stock price. However, there are negative relationship between currency and stock price in each country.